2020
DOI: 10.1021/acsaem.0c01534
|View full text |Cite
|
Sign up to set email alerts
|

Potential-Dependent Layering in the Electrochemical Double Layer of Water-in-Salt Electrolytes

Abstract: Water-in-salt electrolytes (WiSE) are concentrated aqueous electrolytes recently developed that are of great interest because of their possible relevance for batteries. The origin for their promising application has been ascribed to the formation of percolating nanodomains in the bulk. However, the interfacial structure of WiSE still remains to be understood. In this paper, we characterize the potential-dependent double layer of a LiTFSIbased electrolyte on a charged electrode surface. Ultramicroelectrode (UME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
62
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(76 citation statements)
references
References 70 publications
13
62
1
Order By: Relevance
“…IR studies were found to be in agreement with these theoretical predictions [74] . In a more detailed vibrational spectroscopy investigation, it was found that the interface structure in 21 m LiTFSI water‐in‐salt electrolyte depends on applied potential, [75] as illustrated schematically in Figure 6b. Furthermore, AFM measurements at various potentials revealed the formation of a thick layer (in the range of 6.5 Å) at positive potentials due to the presence of large TFSI anions that evolved to a thinner layer consisting of water molecules and hydrated Li + .…”
Section: Electrochemical Propertiessupporting
confidence: 65%
See 3 more Smart Citations
“…IR studies were found to be in agreement with these theoretical predictions [74] . In a more detailed vibrational spectroscopy investigation, it was found that the interface structure in 21 m LiTFSI water‐in‐salt electrolyte depends on applied potential, [75] as illustrated schematically in Figure 6b. Furthermore, AFM measurements at various potentials revealed the formation of a thick layer (in the range of 6.5 Å) at positive potentials due to the presence of large TFSI anions that evolved to a thinner layer consisting of water molecules and hydrated Li + .…”
Section: Electrochemical Propertiessupporting
confidence: 65%
“…Hence, the structure of the ions and solvent in water‐in‐salt electrolyte, as presented above, is likely to have an impact on their structure at the electrode surface. Insight to the structure of the electrified interface is obtained by modeling, [72–74] vibrational spectroscopy, [74,75] and atomic force microscopy (AFM) [75] …”
Section: Electrochemical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…salt-in-ILs (SiILs) [7][8][9][10][11][12][13], which increases the energy that can be stored in the device. The promise of IL-based technologies has caused significant interest in understanding ILs, and other concentrated electrolytes, such as water-in-salt electrolytes (WiSEs) [14][15][16][17][18][19][20][21][22][23][24]. Indeed, owing to the high concentration and lack of high dielectric solvent, the energy of electrostatic interactions between nearest neighbors is much larger than thermal energy [3].…”
Section: Introductionmentioning
confidence: 99%